Pembinaan Narapidana Dengan Sistem Pemasyarakatan - Doris Rahmat (Law Faculty of Universitas Bandar Lampung, 2018)
The institution of society is a place that is used in Indonesia which is emphasized on the aspect of coaching. In this penitentiary the prisoners are nurtured and educated and equipped with knowledge and skills as a provision for him when he finishes his penalty. With this provision the prisoner can return to the community and become a good member and able to be responsible, The research method used is the method of sociological juridical approach that is the problem approach through legal research by looking at the reality of the law in practice, while the data collection tool used in this research is interview, collect primary and secondary data, then Analyzed Qualitatively By Grouping Data According To Aspects Studied.